The role of the United Nations in protecting the right to development in occupied Palestine - Alasttal, Abdelrahman; Magassing, Abdul Maasba; Maskun, Maskun; Sakharina, Iin Karita (Legality : Jurnal Ilmiah Hukum, 2023)
Talking about human rights in the absence of development is nonsense. Therefore, Palestinian human rights are deficient due to the disruption of development in the occupied Palestinian territories. The purpose of this study is principally to analyze the obstacles to the development process in Palestine, examine the scope of the role of the United Nations in supporting development in Palestine under Israeli occupation, and compare that with its role in Rakhine. The methodology refers to a comparative analytical study and a statutory and conceptual approach, revealing that the existence of the Israeli occupation is considered the main obstacle to development in Palestine; and the role of the United Nations has been ineffective to date in ending this occupation; therefore, the role of the United Nations in protecting the Palestinians' right to development is very limited, as the realization of the right to development is linked to the realization of the right to self-determination for the Palestinian people. Development requires the unification of regions and the optimal exploitation of natural resources, but this is not possible in Palestine because of the policies of the Israeli occupation in building settlements, imposing a complete blockade on the Gaza Strip and separating it from the West Bank, and dividing the West Bank into areas of influence, as well as imposing complete control over the natural resources and preventing the Palestinians from benefiting from them, with the aim of keeping the Palestinian economy weak and under Israeli control, thereby keeping the Palestinian decision under the influence of Israel. In conclusion, the role of the United Nations is ineffective in supporting development in Palestine and Rakhine, due to the inability of the Security Council to take any effective action due to the disagreement of the permanent members.